2018
DOI: 10.1371/journal.pone.0200856
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of malaria Rapid Diagnostic Tests’ utilisation among healthcare workers in Zamfara State

Abstract: IntroductionEarly diagnosis and prompt and effective treatment is one of the pillars of malaria control. Malaria case management guidelines recommend diagnostic testing before treatment using malaria Rapid Diagnostic Test (mRDT) or microscopy and this was adopted in Nigeria in 2010. However, despite the deployment of mRDT, the use of mRDTs by health workers varies by settings. This study set out to assess factors influencing utilisation of mRDT among healthcare workers in Zamfara State, Nigeria.MethodsA cross-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
(26 reference statements)
3
8
0
Order By: Relevance
“…This study is in sequel to an earlier report (Abdullahi et al, 2009). There were similar malaria researches in Zamfara State (Moyi et al 2013, Garba et al, 2014, Usman et al, 2018, Abdulkadir et al, 2015, Maigemu & Hassan, 2015 but none these studies is as detailed as this study. The study looked at the knowledge, attitude, perception and practices of the population of Gusau metropolis on malaria and malaria control.…”
Section: Introductionsupporting
confidence: 75%
“…This study is in sequel to an earlier report (Abdullahi et al, 2009). There were similar malaria researches in Zamfara State (Moyi et al 2013, Garba et al, 2014, Usman et al, 2018, Abdulkadir et al, 2015, Maigemu & Hassan, 2015 but none these studies is as detailed as this study. The study looked at the knowledge, attitude, perception and practices of the population of Gusau metropolis on malaria and malaria control.…”
Section: Introductionsupporting
confidence: 75%
“…The study by Ndibuagu et al [13], in which 90.7% of respondents were aware of parasitological examination of blood to be the WHO recommended approach of establishing malaria diagnosis corroborates this finding from current research. Also a study done by Usman Rabi et al [14] reported more than half of respondents had good knowledge of mRDT in tandem with above finding. This calls for training of community pharmacist on the WHO T3 initiative as community pharmacist will be better equipped with knowledge to handle malaria case management.…”
Section: Discussionmentioning
confidence: 60%
“…The findings from this study which revealed that 28.5% of community pharmacists carry out malaria diagnosis with a confirmatory test before commencing treatment and 90% of the respondents indicated that they treat malaria based on clinical signs and symptoms only (presumptive/ syndromic treatment) is substantiated by results of a study conducted by Uzochukwu et al [15] in South Eastern Nigeria which reported that majority of health facilities practiced presumptive malaria case management. In contrast, a study conducted by Usman Rabi et al [14] on availability and use of mRDT in public health facilities reported 82.7% of the healthcare workers employed malaria RDT routinely before making a diagnosis of malaria This may be largely due to public health facilities are less likely to commence treatment without diagnosis than private owned pharmacies which are profit-oriented. Malaria Rapid Diagnostic Test (mRDT) and a combination of mRDT and microscopy were the most common confirmatory test carried out.…”
Section: Discussionmentioning
confidence: 90%
“…Sample size of 220 was estimated using 95% level of confidence, 5% level of precision, 82.7% as the expected proportion (based on the proportion of public health workers that routinely use MRDT for the diagnoses of malaria in a previous study [ 31 ], and the sample size formula for single proportion. Provision was made for a response rate of 90% by dividing the calculated sample size of 220 by 0.9 to get 245.…”
Section: Methodsmentioning
confidence: 99%
“…There is relative paucity of literature on the use of MRDT and anti-malarial drug prescription practices and their predictors. Although some studies in Nigeria had assessed the use of MRDT among health workers [ 23 25 , 31 ], only few assessed the malarial drug use pattern [ 27 , 28 ] and there was marked variation in the reported use of MRDT and anti-malarial drug prescription practices. Also, the use of MRDT, especially at the PHC level, has made universal access to parasitological diagnosis of malaria possible [ 5 ].…”
Section: Introductionmentioning
confidence: 99%